Communicative Governance and Integrated Marketing Communication in the OVOP Policy: A Case Study of NTT Mart, East Nusa Tenggara - Adellia Agusta; Descorina Priscillia Br Sitompul; Roidah 'Afro; Zulkifli Djamaluddin Umar; Yuan Elim Valentino; Sirilus M. Lelan; Mariano AT Nugraha (INJECT (Interdisciplinary Journal of Communication), 2026)
Public policy implementation in geographically fragmented and institutionally uneven regions depends not only on regulatory design and infrastructure provision, but also on effective institutional communication. In East Nusa Tenggara (NTT), an archipelagic province characterized by high poverty rates and strong dependence on micro, small, and medium enterprises (MSMEs), local economic development policies face structural challenges related to distribution barriers, multi-actor coordination, and digital inequality. Within this context, communication becomes central to aligning stakeholders and integrating policy objectives. Although Integrated Marketing Communication (IMC) is widely discussed in corporate marketing literature, its application in public policy implementation remains underexplored. This study analyzes the implementation, strategic role, and challenges of IMC in supporting the One Village One Product (OVOP) policy through the NTT Mart initiative. Using a qualitative case study approach based on institutional documents and digital communication analysis, the research examines how IMC operates within a peripheral governance setting. The findings show that IMC functions not merely as a promotional tool, but as a governance infrastructure that integrates multi-channel communication, stakeholder coordination, and policy narratives. However, its effectiveness is constrained by geographical fragmentation, digital divides, uneven institutional capacity, and limited operational transparency. The study contributes to communicative governance theory by positioning IMC as a structural determinant of policy implementation in developing, archipelagic governance contexts.